PERANAN GURU PENDIDIKAN AGAMA ISLAM DAN GURU BIMBINGAN KONSELING DALAM PENGEMBANGAN KEPRIBADIAN SISWA - Tangkiyahs (Adz-Zikr : Jurnal Pendidikan Agama Islam, 2023)
personality is a unique characteristic that is owned by a person, in the development of personality is influenced by various factors including the role of the teacher. The purpose of this study was to describe the personality of students, the role of the teacher, the obstacles encountered, as well as the efforts made by Islamic Religious Education teachers and Counseling Teachers in developing student personalities. The method used is a descriptive method with a qualitative approach. Collection techniques with interviews, observation, documentation, and questionnaires. The analysis technique was carried out by data reduction, data presentation, data validity by triangulation, and drawing conclusions or verification.The results of the study showed that in general the personality of students at SMAN 4 Cilegon City from the aspects of honest, disciplined, responsible, tolerant, and helpful personalities was good. The roles played by Islamic Religious Education teachers are as educators, educators, mentors, directors, assessors, evaluators, and also as motivators. Counseling Guidance Teachers have provided orientation, information, placement and solution services, learning, counseling, guidance groups, case conferences, and services with guidance boards, besides that they have collaborated with teachers, parents, and related parties. The obstacle faced by Islamic Religious Education teachers is evaluating the program. Counseling Guidance teacher constraints there is only one teacher and it has not been scheduled to be able to enter class